Measurement of the semileptonic branching ratio of Bs0 to an orbitally excited Ds** state: Br(Bs0→Ds1-(2536)μ+νX) - Abazov, V. M. (2009)
In a data sample of approximately 1.3fb-1 collected with the D0 detector between 2002 and 2006, the orbitally excited charm state Ds1±(2536) has been observed with a measured mass of 2535.7±0.6(stat)±0.5(syst) MeV/c2 via the decay mode Bs0→Ds1-(2536)μ+νμX. A first measurement is made of the branching ratio product Br(b̄→Ds1-(2536) μ+νμX)×Br(Ds1-→D*-KS0). Assuming that Ds1-(2536) production in semileptonic decay is entirely from Bs0, an extraction of the semileptonic branching ratio Br(Bs0→Ds1-(2536)μ+νμX) is made. © 2009 The American Physical Society.